Deep pyoderma caused by Burkholderia cepacia complex associated with ciclosporin administration in dogs: a case series. Issue 4 (12th May 2015) - Banovic, Frane; Koch, Sandra; Robson, David; Jacob, Megan; Olivry, Thierry
<x xml:space="preserve">Abstract</x> Background Bacteria of the Burkholderia cepacia complex (Bcc) are ubiquitous Gram‐negative bacilli associated with fatal nosocomial infections in humans; multi‐antibiotic resistance makes this organism a serious threat in hospital settings. Objective To describe the historical, clinicopathological and treatment characteristics of Bcc‐associated deep skin infections in dogs. Animals Six dogs with skin infections in which skin bacterial cultures resulted in pure growth of Bcc. Methods Retrospective study with review of medical records and skin biopsies. Results All dogs were receiving oral ciclosporin at the time of skin infection development. All dogs were castrated males and four of six were West Highland white terriers. Cutaneous lesions consistent with deep pyoderma were confined mainly to the trunk. In all dogs skin cytology revealed a strong inflammatory response, with moderate to abundant numbers of intracellular (neutrophils and macrophages) and extracellular bacilli. In three dogs histopathology showed a multifocal, nodular to coalescing pyogranulomatous dermatitis associated with multifocal folliculitis and furunculosis. Tissue Giemsa and Gram stains identified numerous Gram‐negative rods within macrophages. Antimicrobial susceptibility testing revealed multidrug‐resistant Bcc strains with sensitivity to trimethoprim/sulfonamides in all dogs and to marbofloxacin, piperacillin and ceftazidime in three dogs. Successful treatment was achieved in all dogs using trimethoprim/sulfonamides or quinolones (marbofloxacin, ciprofloxacin) or doxycycline in conjunction with ciclosporin withdrawal. Conclusions and clinical importance Clinicians should be aware of the rare potential for Bcc‐associated deep skin infections in dogs receiving oral ciclosporin. Owners should be made conscious of the potential transmission risk to humans or other animals.